태양열 계간축열조에 변유량 및 변위치 제어를 적용한 효과 - 김종현(Jong-Hyun Kim); 한유정(You-Jung Han); 김철(Chul Kim); 홍희기(Hiki Hong) (설비공학 논문집, 30(12), 2018)
STES (Seasonal Thermal Energy Storage) is one of the most effective ways to improve the performance of the solar thermal system in the summer season. During the summer, the STES system stores thermal energy owing to low thermal demand and then uses in the winter when the thermal demand is high. Stratification in the storage tank can enhance the thermal efficiency of the system. In general, there are two methods for stratification; to control the flow rate and to apply devices such as diffuser and distributor. In this study, we propose a simple method which controls the flow rate and the inlet port position. Experiments and simulation were carried out to investigate the performance and effect of the proposed method. It was confirmed that the temperature reversal phenomenon can be prevented, and the stratification index and the solar fraction are improved by the combined control with a variable flow rate and a variable position controls. KCI Citation Count: 1